2016
DOI: 10.3389/fpls.2016.01761
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Dolabellane Type Diterpene Synthase and other Root-Expressed Diterpene Synthases in Arabidopsis

Abstract: Arabidopsis thaliana maintains a complex metabolism for the production of secondary or specialized metabolites. Such metabolites include volatile and semivolatile terpenes, which have been associated with direct and indirect defensive activities in flowers and leaves. In comparison, the structural diversity and function of terpenes in Arabidopsis roots has remained largely unexplored despite a substantial number of root-expressed genes in the Arabidopsis terpene synthase (TPS) gene family. We show that five ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 70 publications
0
23
1
Order By: Relevance
“…S2B). However, we did not observe the formation of sesquiterpenes or diterpenes, even for AtTPS22, -25, -29, and -30, which had previously been reported to synthesize these types of terpenes in vitro (31). This outcome may be because of the low activity of the encoding enzymes, inadequate precursor supply, or the loss of the volatile/semivolatile products in N. benthamiana, especially if these products were produced in very low abundance.…”
Section: Resultscontrasting
confidence: 75%
See 2 more Smart Citations
“…S2B). However, we did not observe the formation of sesquiterpenes or diterpenes, even for AtTPS22, -25, -29, and -30, which had previously been reported to synthesize these types of terpenes in vitro (31). This outcome may be because of the low activity of the encoding enzymes, inadequate precursor supply, or the loss of the volatile/semivolatile products in N. benthamiana, especially if these products were produced in very low abundance.…”
Section: Resultscontrasting
confidence: 75%
“…N-terminal transit peptide (N-tp)-truncated recombinant AtTPS18 and AtTPS19 proteins were recently coexpressed with N-tp AtGFPPS1 and AtGFPPS2 in E. coli and reported to synthesize (+)-arathanatriene and (−)-retigeranin B, respectively (22). Recombinant proteins encoded by N-tptruncated AtTPS22 and AtTPS25 were also recently expressed in E. coli but reported to have sesquiterpene synthase activity, making sesquiterpene mixtures when incubated with E,E-farnesyl diphosphate (E,E-FPP) as a substrate in vitro (31). Recombinant proteins encoded by N-tp-truncated AtTPS30 were found to have DTS activities when assayed with GGPP or ent-copalyl diphosphate (ent-CPP) as substrates in vitro, whereas AtTPS29 was not active in these assays (31).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main pathway to diterpenoids in angiosperms involves the sequential activity of two TPSs (class II followed by class I) and leads to the formation of the labdane-related diterpenoids (characterised by a decalin core) [23]. Diterpenes can also be biosynthesised directly from geranylgeranyl diphosphate (GGPP) or nerylneryl diphosphate (NNPP, the all cis isomer of GGPP) by class I TPSs alone to generate linear [27,28], macrocyclic [29][30][31] and (poly) cyclic [32][33][34][35] products. These enzymes catalyse metal ion dependant ionization of the diphosphate bond of their prenyl diphosphate substrates to generate a reactive carbocation molecule.…”
Section: Introductionmentioning
confidence: 99%
“…It would be great if possible that the author could add this piece of information, which would be valuable for future characterization of these genes. An example study showing the expression pattern of terpene genes would be found in the paper by Wang, et al 2016 1 .…”
mentioning
confidence: 99%